Factors influencing acceptance of Robo-Advisors for wealth management in Malaysia - Nguyen, Thi Phuong Lan; Li, Woon Chew; Muthaiyah, Saravanan; Boon, Heng Teh; Tze, San Ong (Taylor and Francis Group, 2023)
Since the 2008 global financial crisis, many innovations have emerged in the financial sector as investors started to look for alternative methods to eliminate irrational decision-making in wealth management, and Robo-advisors is among those. Nine years after the first launching of Robo-advisors in the U.S. in 2008, the Securities Commission Malaysia has been issuing licenses to seven Robo-advisor platforms. The current COVID-19 outbreak has made this industry more in demand, increasing 763% in registration in 2020. However, much skepticism about Robo advisors’ ability and reliability in providing a similar quality or better advisory service compared to human-financial advisors. Therefore, this study examines the factors influencing the acceptance of Robo-advisors in wealth management in Malaysia. Adopting some factors from various established technology acceptance models, an online survey with 122 respondents was conducted using convenience sampling. Findings show that Relative Advantage, Effort Expectancy, and Social Influence significantly positive influence the Malaysian Behavioral Intention to Accept Robo-Advisors. On the contrary, there is no significant relationship between Perceived Risk and Malaysian Behavioral Intention to Accept Robo-Advisors. The study provides a positive insight into factors influencing the acceptance of Robo-Advisors in Malaysia.